Outbreak surveillance in a hospital environment: a bibliometric analysis (Research, Society and Development, 2022)
The study of scientific production on the subject of Outbreak Surveillance in the Hospital Environment is extremely relevant, mainly because it indicates an overview of the risks and threats to public health through the epidemiological analysis of the scenario. The aim of this study was to outline an overview of the scientific production on the theme Surveillance of Outbreak in Hospital Environment, in order to identify: the most productive authors (Lotka's Law); the evolution of the number of publications and the journals that published the most on the subject (Bradford's Law); and the main approaches that cover the topic (Zipf's Law). The methodology followed four steps: choosing the Web of Science as the database for consultation; configuration of search strategy parameters and coverage period; debugging of results; and processing of research data. The results showed that between 2017 and 2021 3078 articles were indexed in the Web of Science. Scientific production has been high in the last 2 years. The most productive authors were Weber, David J and Yuen, Kwok-Yung. observed a high concentration in a specific group of authors with low diffusion. It was identified that there are three journals with the highest productivity, accounting for one third of the total scientific production: Journal Of Hospital Infection, Infection Control And Hospital Epidemiology, American Journal Of Infection Control. The main keywords indexed by Web of Science were: Covid-19; Outbreak, Sars-Cov-2, Infection Control, Coronavirus, Epidemiology, Pandemic, directly related to the current pandemic. These bibliometric studies are important to consolidate empirically observed aspects and point out new possibilities and directions for scientific research on Outbreak Surveillance in Hospital Environment.